A Study About Small Scale Business Players' Awareness Intensity On Digital Marketing Trends For Business Promotion In Tamilnadu - Jaiganesh, M.; Sundar, Dr. C. (The journal of contemporary issues in business and government, 2021)
The main aim of business promotion is to magnify the awareness of products or services of the company with the target consumer groups, to build importance with stakeholders and, create brand fidelity among the competitors. Digital marketing provides broad access to explore the internet, digital media or any electronic platform as the medium for business promotion. Exclusively small-size businesses with digital technologies could able to focus on constructing a strong online presence in the world of the internet. This study focuses on various components of digital marketing like search engine marketing, Website optimization, Search engine optimization, Social media advertising, Pay-Per-Click advertising, Email marketing, Content marketing, etc.., To test the awareness level researchers have collects 150 responses that cover core aspects of digital marketing trends. This study shows that small business players are having a great level of awareness about the organic way of digital marketing and fruitfully utilizing the social media platforms for business promotion.